Medidas de confianza mutua y reacercamiento entre Cuba y los Estados Unidos - Klepak, Hal P. (Estudios Internacionales, 1994)
Mutual trust and security measures between nations (known as CSBM or CBM), have been incorporating a series of procedures whose ultimate purpose is to alleviate tensions and lessen the danger of an armed conflict breaking out as a consequence of a misinterpretation or miscalculation about the maneuvers of a rival state. In the present work, they are situated in the context of the current relations between Cuba and the United States, in order to consider whether it makes sense to seek CBMs that could reduce tension and create a more conducive political environment to improve relations between Havana and Washington. It is also analyzed whether there are no other ways, different from the one defined by these initiatives, to initiate a rapprochement process that future CBMs could later accelerate or consolidate.